Female narratives in Nollywood melodramas - Johnson, Elizabeth 1966-; Culverson, Donald R. 1951- (Lexington Books, 2016)
"Female Narratives in Nollywood Melodramas investigates the role of women in nine Nollywood melodramas with attention to the changing landscape of filmmaking and film viewing. By incorporating Black feminist, audience reception, social identity, and cultivation theories, Johnson and Culverson provide insight into how identities for West African women are created and recreated through the broad interplay of Nollywood film viewing on social and individual levels. This book addresses how Nollywood is a product and contributor to evolving processes of globalization."...